Integrasi HAM dan Hukum Humaniter dalam Sistem Peradilan HAM Nasional dalam Rangka Penerapan Peradilan HAM terhadap Pelaku Kejahatan Kemanusiaan - Mahfud Mahfud (Universitas Syiah Kuala, 2013)
ABSTRACT: The law enforcement of Human right in Indonesia result in internal dinamic to response international positive influence. Indonesia has a real of legal system of regulation human right case in Indonesia. It can be seen in the implementation of the Act. Number 39, 1999 regarding Human Right Act. The Act Number 26, 2000 regarding Human Right Justice. Implementation of the regulation in Indonesian effort is to avoid international intervention in domestic affair for crimes againt humanity. Mechanism in this regulation is law enforcement of humanitarian law to enforce it based on national justice process. That means, if grave breaches of humanitarian law occurs, the perpetrators’ justice will be processed based on national regulation mechanism. However, international law mechanism will be implentated if national court unwilling and unable to law process criminals for the commission. Integration of Human Right and Humanitarian Law in National Human Right Law Justice System for Implementation of Human Right Justice to Humanity Crimes Doer